PENDEKATAN ESTETIKA DALAM TATA PENCAHAYAAN INTERIOR BAKERY UNTUK MEMBANGUN SUASANA DAN DAYA TARIK VISUAL: AESTHETIC APPROACH IN INTERIOR LIGHTING BAKERY IN BUILDING ATMOSPHERE AND VISUAL APPEAL - Gita Listia; Amarena Nediari (Jurnal Dimensi Seni Rupa dan Desain, 2025)
Lighting design is a fundamental element in shaping the ambiance of retail interiors, which functions to increase visual appeal and influence customer purchasing behavior. Bread as a fresh product is produced for direct sale, requiring display arrangement  lighting techniques that must be able to display the product without  changhing the visual appearance, taste and color of the bread. The study was conducted with a field study at several bakery in Central Park Mall, West Jakarta. Measurement of lighting sources in displaying the bread on display rack includes intensity of light that is falling on the surface in lux, corelated color temperature (CCT) and color rendering index (CRI). This study aims to analyzie how light intensity (lux), CCT and CRI contribute to aesthetically pleasing and functionally effective lighting in bakery interiors. Data collection was obtained from measurements carried out at bakeries of Tous Les Jours, Dynamite and Provence. The results of the study are expected to be a reference in the application of lighting design in bakeries, in building an atmosphere and visual appeal to attract customer to purchase bread and make repeated visit.